The Emergence of Systematic Review in Toxicology - Stephens, Martin L. (Toxicol Sci, 2016)
The Evidence-based Toxicology Collaboration hosted a workshop on “The Emergence of Systematic Review and Related Evidence-based Approaches in Toxicology,” on November 21, 2014 in Baltimore, Maryland. The workshop featured speakers from agencies and organizations applying systematic review approaches to questions in toxicology, speakers with experience in conducting systematic reviews in medicine and healthcare, and stakeholders in industry, government, academia, and non-governmental organizations. Based on the workshop presentations and discussion, here we address the state of systematic review methods in toxicology, historical antecedents in both medicine and toxicology, challenges to the translation of systematic review from medicine to toxicology, and thoughts on the way forward. We conclude with a recommendation that as various agencies and organizations adapt systematic review methods, they continue to work together to ensure that there is a harmonized process for how the basic elements of systematic review methods are applied in toxicology.